Pengukuran Waktu Baku untuk Menentukan Produktivitas Karyawan dengan Menggunakan Metode Jam Henti (Studi Kasus CV. Mulia Tata Sejahtera) - Salman Al Faridzi; Kusnadi Kusnadi; Hamdani Hamdani (Fakultas Teknik, 2022)
A company definitely wants maximum profit in its business. High productivity is needed from employees who work in order to get maximum profit. But lately CV. Mulia Tata Sejahtera in meeting the needs of its consumers sometimes experiences delays from the predetermined schedule due to the large number of orders received, it is necessary to calculate the standard time with the downtime method for one of the products, namely the CPM knife. The purpose of this research is to identify working hours and effective working hours so that companies can increase their productivity and determine their daily production. The results of the research carried out obtained that the total standard time in making CPM Knives products was 70.86 minutes and employee productivity in making CPM Knives products was that a worker could complete 6.7 units of CPM Knives in 8 hours/day. Based on the calculation of the standard time it was decided to be 6 units/day so that there was a reduction in working hours for 49.79 minutes from 8 hours/day to 7 hours 10.21 minutes/day.